2008
DOI: 10.1007/s00595-007-3755-6
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysm surgery for octogenarians

Abstract: We concluded that AAAs over 6 cm in diameter were an appropriate indication for surgery in octogenarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…In our previous report, AAAs smaller than 6 cm at diagnosis rarely ruptured, and most patients eventually died of nonaneurysmal disease. 13 According to Japanese vital statistics, death from aortic disease accounts for only 1.2% of total deaths. 14 Although it is important to note that endovascular repair of AAA was associated with a signifi cantly lower rate of aneurysm-related mortality than no repair, it is unreasonable to expect a signifi cant reduction in the rate of total deaths from any cause given this low percentage.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, AAAs smaller than 6 cm at diagnosis rarely ruptured, and most patients eventually died of nonaneurysmal disease. 13 According to Japanese vital statistics, death from aortic disease accounts for only 1.2% of total deaths. 14 Although it is important to note that endovascular repair of AAA was associated with a signifi cantly lower rate of aneurysm-related mortality than no repair, it is unreasonable to expect a signifi cant reduction in the rate of total deaths from any cause given this low percentage.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 EVAR has several advantages over traditional open surgery in appropriately selected patients. 5,6 However, a hostile proximal neck (PN), including severe angulation, short neck, and reverse funnel neck, is still considered a major anatomic limitation for EVAR. Several investigators have reported that severe angulation of the PN affected the outcomes of EVAR, including type Ia endoleak and migration.…”
mentioning
confidence: 99%
“…Table 5 summarizes the current literatures of treatment for AAA in octogenarians. [4][5][6][7][8]12,[15][16][17][18][19][20][21][22][23][24][25] In this study, the incidence of CAD was 33.8%. The percentage of CAD varies by reports or countries, 21-33.3% in Japan 20,23 and 34-69% in US, [5][6][7][8]16,24,25 which may be caused by the difference of the lifestyle.…”
Section: Discussionmentioning
confidence: 99%